Talorchestia buensis sp. nov. (Senticaudata, Talitridae), a new species of amphipod from West Bengal, east coast of India - Bhoi, Gitanjali; Myers, Alan A.; Khatua, Rohit; Patro, Shesdev (Zootaxa, 2023)
In coastal regions, Talitrids are found among decaying material in the supralittoral zone of sandy beach, mangroves and delta regions. Five genus and five species of the family Talitridae have been reported so far from Indian coastal waters. A new species of the amphipod genus Talorchestia Dana, 1852, Talorchestia buensis sp. nov. was collected from Kadirabad Char, West Bengal, east coast of India. The species was collected from a sandy beach, beneath dead leaves. The new species can be distinguished from other described species of the genus by the presence of a double rows of setae on the endopod of uropod 2, the presence of more than 10 robust setae in each lobe of the telson, antenna 2 reaching more than half the body length, pereopod 7 longer than pereopod 6 and by the absence of a distal protuberance on the palm of male gnathopod 2. The present article increases the total number of world species in the genus to 26.